2008
DOI: 10.1111/j.1751-553x.2007.00953.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐inheritance of haemoglobin A2′ and beta‐thalassaemia in cis

Abstract: HbA2' is a haematologically silent delta chain variant that elutes in the S-region on high performance liquid chromatography. The major clinical significance of HbA2' is that failure to detect it might lead to failure to recognize beta-thalassaemia minor. Co-inheritance of HbA2' and beta-thalassaemia in cis has been described only once in a family from Suriname. We describe a new case of co-inheritance in cis of HbA2' and beta-thalassaemia in a family from Ghanaian origin with a HbA2' of more than 3%. Molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The levels of HbA2 were found to be higher than those of HbA2' in all cases similar to other published reports [2,6,14,16]. All cases with suspected HbA2' of >2% fell under the category of β-thalassaemia minor if S-window peak was taken into account, which was also consistent with previously published studies [10,14]. Despite the similarities of our HPLC chromatogram analysis with HbA2'studies published earlier, the mutation was absent on genetic analysis.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The levels of HbA2 were found to be higher than those of HbA2' in all cases similar to other published reports [2,6,14,16]. All cases with suspected HbA2' of >2% fell under the category of β-thalassaemia minor if S-window peak was taken into account, which was also consistent with previously published studies [10,14]. Despite the similarities of our HPLC chromatogram analysis with HbA2'studies published earlier, the mutation was absent on genetic analysis.…”
Section: Resultssupporting
confidence: 91%
“…Many studies have reported double heterozygotes with HbA2' levels of >2% [2,6] and as high as 3.3% [10]. Blood transfusions in sickle cell disease may dilute HbS to as low as 2.6% [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through genetic counseling and the option of prenatal testing, such a couple can opt to bring to term only those pregnancies in which the fetus is unaffected. Elevation of HbA 2 is the most important feature in the detection of heterozygous b-thalassemia, but there are sometimes bthalassemia heterozygotes with normal HbA 2 , compromising the screening effectiveness [1][2][3][4][5]. b-thalassemia with the absence of HbA 2 is very rare.…”
mentioning
confidence: 99%